Risk Factors Associated with the incidence of ISPA in Toddlers (1-5 Years) in the Working Area of North Singkil Health Center, Aceh Singkil Regency - Syahriazi; Fahdhienie, Farrah; Ariscasari, Putri (International Journal of Applied Research and Sustainable Sciences, 2024)
Upper respiratory tract infection (ARI) is a disease of the upper or lower respiratory tract, which is contagious and can cause a wide spectrum of diseases from asymptomatic to severe and deadly disease. The research aimed to determine the risk factors associated with the incidence of ISPA in toddlers in the North Singkil Community Health Center Working Area, Aceh Singkil Regency. This research is analytical with a case-control research design. Data collection was carried out by interviews using questionnaires. The population in this study was 116 toddlers with a sampling technique, namely Simple Random Sampling. Data collection was carried out on 18-26 July 2023. The analysis used was univariate and bivariate using the Chi-Square and OR statistical tests. The research results show that cigarette smoke is associated with the incidence of ARI with a p-value of 0.001, OR 4.424, LBW p-value 0.004, and OR 3.367, knowledge with a p-value of 0.002, and OR 3.670, immunization status with a p-value of 0.001, and OR 3.868, breastfeeding with p value 0.005, and OR 3.148. Conclusion There is a relationship between cigarette smoke, LBW, immunization status, and breastfeeding with ARI in toddlers. It is hoped that research sites will provide health education about ISPA by holding health education.